The effect of minority status and social context on the development of depression and anxiety: a longitudinal study of Puerto Rican descent youth. Issue 3 (9th September 2019) - Alegria, Margarita; Shrout, Patrick E.; Canino, Glorisa; Alvarez, Kiara; Wang, Ye; Bird, Hector; Markle, Sheri Lapatin; Ramos‐Olazagasti, Maria; Rivera, Doryliz Vila; Cook, Benjamin Lê; Musa, George J.; Falgas‐Bague, Irene; et al.
Abstract : Few longitudinal studies have explored to date whether minority status in disadvantaged neighborhoods conveys risk for negative mental health outcomes, and the mechanisms possibly leading to such risk. We investigated how minority status influences four developmental mental health outcomes in an ethnically homogeneous sample of Puerto Rican youth. We tested models of risk for major depressive disorder (MDD) and generalized anxiety disorder (GAD), depressive and anxiety symptoms (DAS), and psychological distress, as Puerto Rican youth (aged 5‐13 years) transitioned to early adulthood (15‐29 years) in two sites, one where they grew up as a majority (the island of Puerto Rico), and another where they were part of a minority group (South Bronx, New York). At baseline, a stratified sample of 2, 491 Puerto Rican youth participated from the two sites. After baseline assessment (Wave 1), each youth participant and one caregiver were assessed annually for two years, for a total of three time points (Waves 1‐3). From April 2013 to August 2017, participants were contacted for a Wave 4 interview, and a total of 2, 004 young people aged 15 to 29 years participated in the assessment (response rate adjusted for eligibility = 82.8%). Using a quasi‐experimental design, we assessed impacts of minority status on MDD, GAD, DAS and psychological distress. Via mediation analyses, we explored potential mechanisms underlying the observed relationships. Data from 1, 863 Puerto Rican youth (after exclusion of those with MDD or GAD during Waves 1‐3) indicated links between minority status and higher rates of lifetime and past‐year GAD, DAS and past 30‐day psychological distress at Wave 4, and a marginal trend for MDD, even after adjustments. Childhood social support and peer relationships partially explained the differences, as did intercultural conflict, neighborhood discrimination, and unfair treatment in young adulthood. The experience of growing up as a minority, as defined by context, seemingly elevates psychiatric risks, with differences in social relationships and increased social stress as mediators of this relationship. Our findings suggest that interventions at the neighborhood context rather than at the individual level might be important levers to reduce risks for the development of mood disorders in minority youth.